The Influence of Workload and Placement on the Work Productivity of Ad-Hock Agency Employees - Ayu Anora; Yusnidar; Surya Darni (Universitas Serambi Mekkah, 2024)
The purpose of this study was to determine the magnitude of the influence of workload on the work productivity of the adhock body of Panwaslu District and Village of Banda Sakti District of Lhokseumawe City, the influence of placement on the work productivity of the adhock body of Panwaslu District and Village of Banda Sakti District of Lhokseumawe City and the magnitude of the influence of load on performance and placement simultaneously on work productivity / employee performance at the adhock body of Panwaslu District and Village of Banda Sakti District of Lhokseumawe City. This research was conducted at the adhock Panwaslu sub-district and village agencies in the Banda Sakti sub-district of Lhokseumawe City. The object of this research is workload, placement and work productivity of adhock bodies. The sample in this study amounted to 88 respondents. Data collection in the study using a questionnaire on a Likert scale unit. In this study, the analytical equipment used is multiple linear regression and hypothesis testing is used, namely the F-test and t-test using the SPSS version 15.0 test tool. From the results of the F-test (simultaneous) and t-test (partial) it can be seen that all the variables studied workload and placement have a significant influence on increasing the work productivity of the adhock body of Panwaslu District and Village in the Banda Sakti District of Lhokseumawe City where Fhitung is 48.040 where Ftabel is 3.103 at the significance level  = 5%. In the coefficient of determination (adjusted Rsquare) the regression results are 0.520 where it is seen that the workload variable (X1), placement (X2) it is clear that the value of 52.0% on the variable increase in work productivity of the adhock body (Y), where the remaining 48.0% is influenced by factors not examined in this study.